Recent advances in the anti-HCV mechanisms of interferon - Menghao Huang; Jian-Dong Jiang; Zonggen Peng (Elsevier, 2014)
Interferon (IFN) in combination with ribavirin has been the standard of care (SOC) for chronic hepatitis C for the past few decades. Although the current SOC lacks the desired efficacy, and 4 new direct-acting antiviral agents have been recently approved, interferons are still likely to remain the cornerstone of therapy for some time. Moreover, as an important cytokine system of innate immunity, host interferon signaling provides a powerful antiviral response. Nevertheless, the mechanisms by which HCV infection controls interferon production, and how interferons, in turn, trigger anti-HCV activities as well as control the outcome of HCV infection remain to be clarified. In this report, we review current progress in understanding the mechanisms of IFN against HCV, and also summarize the knowledge of induction of interferon signaling by HCV infection.